Level of Awareness of Proper Body Mechanics among Maintenance Personnel of Pamantasan ng Lungsod ng Maynila - Abelita, Anthony B.; Martinez, Raceli Bobbie B.; Nepomuceno, Angelo R.; Padilla, Donita Raye T; and Raper, Dianne Marie D. 4 0 16; 5 (2011)
u
Undergraduate (Thesis) Pamantasan ng Lungsod ng Maynila;College of Physical Therapy, Bachelor of Science in Physical Therapy
Keywords: 2 -- 0; 6; 20; 20; 2